Opportunities and Challenges to Improve National Milk Production - Sori B Siregar (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
National milk production is still unable to fulfil the demand of milk from year by years. Imported dairy cows were able to increase national milk production, but it hasn't able yet to meet the demand of milk that is increased each year. Therefore, national milk production must be increased significantly in order to reduce the gap between national milk production and the demand of milk step by step in the coming years. The opportunities to increase national milk production are still feasible. The recommendation of importing dairy cows is good to continue, increased calving rate has to be planed and reducing mortality rate must be conducted for increasing dairy cows population and the national milk production. The opportunities for increasing national milk production in the form of improving feed management and intensifying artificial insemination have not been implemented optimally. Feed improvement management could be created through increasing quantity and quality of feed, giving opportunity of increasing national milk production about 23,85%. The wide open opportunities to increase national milk production are not free from amount of challenges. The price of milk is still low, the limit of forage production, uneconomical dairy scale farming, unsatisfied livestock breeding, the lack of capital, the competitive of milk import, inefficient management of milk cooperative are the significant challenges in increasing national milk production.   Key words: Dairy cattle, milk production, supply and demand